Enhanced quality of life and smart living : 15th International Conference, ICOST 2017, Paris, France, August 29-31, 2017, Proceedings /: 15th International Conference, ICOST 2017, Paris, France, August 29-31, 2017, Proceedings. (2017) - Unknown
No abstract available